2016
DOI: 10.15835/buasvmcn-vm:11344
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Ticks and Fleas of Dogs in the Western Balkans – Preliminary Examinations

Abstract: Ticks and fleas infestation is the most common ectoparasitic condition of dogs with worldwide distribution. In period 2011-2013 we performed preliminary study on the biodiversity of ticks and flea of dogs, from the Western Balkan area. Parasites were collected from dogs in veterinary practices from several cities in various part of Serbia, Macedonia, Republic Srpska (BiH) and Montenegro. During of the study of relative abundance analysis revealed that the species Ixodes ricinus was absolutely dominant, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…This data is in correlation with the results of other examinations of the seasonal dynamics of ticks in Europe (Belozerow, 1982;Černy et al, 1974;Daniel,1978;L'Hostis et al, 1995;Maroli et al, 1996;Papazahariadou et al,2003;Estrada-Peña et al, 2011). This agrees with the data published about ticks in various part of Russia, Central Europe and the West Balkans (Belozerow, 1982;Dautel et al, 2008;Kolonin, 2009;Omeragić, 2011;Sevinc et al, 2013;Pavlović et al, 2014;2016c). The authors point out that the low temperature, high humidity and rainfall significantly affect the life cycle of ticks, particularly the I. ricinus species.…”
Section: Results and Discusionsupporting
confidence: 87%
“…This data is in correlation with the results of other examinations of the seasonal dynamics of ticks in Europe (Belozerow, 1982;Černy et al, 1974;Daniel,1978;L'Hostis et al, 1995;Maroli et al, 1996;Papazahariadou et al,2003;Estrada-Peña et al, 2011). This agrees with the data published about ticks in various part of Russia, Central Europe and the West Balkans (Belozerow, 1982;Dautel et al, 2008;Kolonin, 2009;Omeragić, 2011;Sevinc et al, 2013;Pavlović et al, 2014;2016c). The authors point out that the low temperature, high humidity and rainfall significantly affect the life cycle of ticks, particularly the I. ricinus species.…”
Section: Results and Discusionsupporting
confidence: 87%
“…In Serbia, of the 1484 dogs brought to clinics from several cities 26.3% were infested with fleas of which 71.9% were C. felis . The highest infestation rates were from June to October [ 79 ]. In Greece, 13.7% of fleas collected from dogs were C. felis , the remaining being C. canis [ 80 ].…”
Section: Cat Flea Biology and Ecologymentioning
confidence: 99%
“…Tick species identified on dogs in this study had previously been identified on domestic dogs in the Vojvodina region, in which I. ricinus and R. sanguineus were the most prevalent tick species [ 19 ]. I. ricinus and R. sanguineus are among the most common ectoparasites found infesting dogs and goats in Serbia, as well as in other countries in the Balkans such as North Macedonia, Montenegro, Romania and, Bosnia and Hercegovina [ [20] , [21] , [22] , [23] ]. Infestations with R. sanguineus in houses is frequently reported in the literature [ [24] , [25] , [26] , [27] ].…”
Section: Discussionmentioning
confidence: 99%